
It's more natural to consider the cross product of no sets to be [[]] so
your crossr becomes:
crossr [] = [[]]
crossr (x:xs) = concat (map (\h ->map (\t -> h:t) (crossr tail)) hd)
which we can rewrite with list comprehensions for conciseness:
crossr [] = [[]]
crossr (x:xs) = [ a:as | a <- x, as <- crossr xs ]
then look at the definition of foldr:
foldr f z [] = z
foldr f z (x:xs) = f x (foldr f z xs)
and, considering (foldr f z) == crossr, you should derive the definition of
f and z.
On Mon, Nov 24, 2008 at 5:43 AM, Larry Evans
On 11/23/08 13:52, Luke Palmer wrote:
2008/11/23 Larry Evans
: http://www.muitovar.com/monad/moncow.xhtml#list
contains a cross function which calculates the cross product of two lists. That attached does the same but then used cross on 3 lists. Naturally, I thought use of fold could generalize that to n lists; however, I'm getting error:
You should try writing this yourself, it would be a good exercise. To begin with, you can mimic the structure of cross in that tutorial, but make it recursive. After you have a recursive version, you might try switching to fold or foldM.
Thanks. The recursive method worked with: -{--cross.hs-- crossr::[[a]] -> [[a]]
crossr lls = case lls of { [] -> [] ; [hd] -> map return hd ; hd:tail -> concat (map (\h ->map (\t -> h:t) (crossr tail)) hd) } -}--cross.hs--
However, I'm not sure fold will work because fold (or rather foldr1) from: http://haskell.org/ghc/docs/latest/html/libraries/base/Prelude.html#12
has signature:
(a->a->a)->[a]->a
and in the cross product case, a is [a1]; so, the signature would be
([a1]->[a1]->[a1]->[[a1]]->[a1]
but what's needed as the final result is [[a1]].
Am I missing something?
-Larry
_______________________________________________ Haskell-Cafe mailing list Haskell-Cafe@haskell.org http://www.haskell.org/mailman/listinfo/haskell-cafe